(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Around 800 women die from preventable causes related to pregnancy and childbirth. 99% of all these deaths occur in developing countries. Various strategies like RCH-II had been successful in halting the progress of maternal mortality, but we still lag behind from our counterparts. The utilization of all components of RCH is necessary to accomplish the goal. As the utilization also depends on awareness levels of beneficiaries, the authors undertook this study to determine knowledge levels of women regarding RCH services